The effect of an equine-assisted positive psychology intervention on flourishing, meaning and hope in an under-resourced South African context : a mixed methods study - Coetzee, Nicoleen (University of Pretoria, 2025)
Thesis (PhD (Psychology))--University of Pretoria, 2024.